2021
DOI: 10.3390/v13081436
|View full text |Cite
|
Sign up to set email alerts
|

Virucidal Efficacy of Blue LED and Far-UVC Light Disinfection against Feline Infectious Peritonitis Virus as a Model for SARS-CoV-2

Abstract: Transmission of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) occurs through respiratory droplets passed directly from person to person or indirectly through fomites, such as common use surfaces or objects. The aim of this study was to determine the virucidal efficacy of blue LED (405 nm) and far-UVC (222 nm) light in comparison to standard UVC (254 nm) irradiation for the inactivation of feline infectious peritonitis virus (FIPV) on different matrices as a model for SARS-CoV-2. Wet or dried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
1
6
1
1
Order By: Relevance
“…The required log irradiation doses for this bovine coronavirus noted here were about an order of magnitude higher than results for SARS-CoV-2 [26,27] and about a factor of 2.5 higher than the results for feline infectious peritonitis virus, another animal coronavirus [54]. However, our determined log reduction doses seem to be roughly in the same order of magnitude than the recent results of Enwemeka et al, who irradiated the human coronaviruses HCoV-229E and HCoV-OC43 with pulsed violet and blue light and observed a 2.37 and 1.46 log reduction with pulsed 405 nm irradiation, respectively [55].…”
Section: Discussioncontrasting
confidence: 68%
“…The required log irradiation doses for this bovine coronavirus noted here were about an order of magnitude higher than results for SARS-CoV-2 [26,27] and about a factor of 2.5 higher than the results for feline infectious peritonitis virus, another animal coronavirus [54]. However, our determined log reduction doses seem to be roughly in the same order of magnitude than the recent results of Enwemeka et al, who irradiated the human coronaviruses HCoV-229E and HCoV-OC43 with pulsed violet and blue light and observed a 2.37 and 1.46 log reduction with pulsed 405 nm irradiation, respectively [55].…”
Section: Discussioncontrasting
confidence: 68%
“…For example, LED devices emitting visible light in the range of 400-420 nm, 430-460 nm, or 500-780 nm can inactivate a variety of bacteria and effectively inactivate influenza virus (Maclean et al, 2008). Gardner et al have found that irradiation with a wavelength of 405 nm of 16.8 mW/cm 2 -20.8 mW/cm 2 has an inactivation effect on the feline infectious peritonitis virus (FIPV) (Gardner et al, 2021). Considering that strong light intensity may affect the quality of food (Glowacz et al, 2015), we used LED visible light with wavelengths of 450 nm to 780 nm and a light irradiance of 4 mW/cm 2 for the inactivation light source, which effectively decontaminated and degraded the genomic RNA of SARS-CoV-2 pseudovirus on the PE package surface in a frozen environment (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…(30) recently demonstrated successful reductions in SARS‐COV‐2 upon exposure to low irradiance (0.035–0.6 mW cm −2 ) 405‐nm light, and additionally highlighted the increased susceptibility of lipid‐enveloped viruses in comparison with non‐enveloped viruses (identical irradiations achieved 2.3 log 10 reductions in SARS‐COV‐2 after 8 h and just 0.1 log 10 reductions in a non‐enveloped RNA virus after 24 h); suggesting the lipid envelope itself may instigate ROS production. Other studies have similarly demonstrated the susceptibility of SARS‐CoV‐2, or an appropriate surrogate, to 405‐nm light inactivation presented on surfaces and in liquid media, both in the presence and absence of photosensitizers (31–35). Although highly encouraging, these studies have primarily demonstrated inactivation using 405‐nm light at high irradiances (≥78.6 mW cm −2 ) or at low irradiances delivered at a very short distance (~2.3–25.4 cm) from the sample surface (30–35), however, it is of great importance to determine whether inactivation of SARS‐CoV‐2 can be achieved under conditions which more accurately represent those which would be safely and practically implemented for environmental decontamination of communal areas.…”
Section: Introductionmentioning
confidence: 92%